2014
DOI: 10.1371/journal.pone.0104807
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Short-Latency Afferent Inhibition Depends on Digit and Task-Relevance

Abstract: Short-latency afferent inhibition (SAI) occurs when a single transcranial magnetic stimulation (TMS) pulse delivered over the primary motor cortex is preceded by peripheral electrical nerve stimulation at a short inter-stimulus interval (∼20–28 ms). SAI has been extensively examined at rest, but few studies have examined how this circuit functions in the context of performing a motor task and if this circuit may contribute to surround inhibition. The present study investigated SAI in a muscle involved versus u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…Nonetheless, the attentional dissociation observed here is consistent with a differential functional role of afferent input to the PA and AP I-wave circuits. PA SAI is reduced during finger movement with the reduction onset occurring during the preparatory phase (Asmussen et al, 2013) and involved in the surround inhibition of muscles not involved in the planned movement (Voller et al, 2006; Asmussen et al, 2014) suggesting a role in spatial and temporal priming of actions. Again, very little research has investigated the functional significance of the AP circuit however, the selective sensitivity of AP SAI to our attention manipulation is consistent with a modulatory mechanism that provides a substrate for cognitive influence upon selected actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the attentional dissociation observed here is consistent with a differential functional role of afferent input to the PA and AP I-wave circuits. PA SAI is reduced during finger movement with the reduction onset occurring during the preparatory phase (Asmussen et al, 2013) and involved in the surround inhibition of muscles not involved in the planned movement (Voller et al, 2006; Asmussen et al, 2014) suggesting a role in spatial and temporal priming of actions. Again, very little research has investigated the functional significance of the AP circuit however, the selective sensitivity of AP SAI to our attention manipulation is consistent with a modulatory mechanism that provides a substrate for cognitive influence upon selected actions.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the positive relationship between the N20-P25 somatosensory evoked potential (SEP) and magnitude of SAI suggests that at least part of the network mediating SAI is dependent upon thalamo-cortical projections to somatosensory cortex (Bailey et al, 2016). Although there is a strong relationship between somatosensory afference and SAI, SAI is a malleable phenomenon modulated by movement timing and the relevance of a muscle to voluntary movement (Voller et al, 2006; Asmussen et al, 2013; Asmussen et al, 2014). Central cholinergic involvement, in addition to GABA A , in the generation of SAI (Ziemann et al, 2014) makes it a potential method to probe the effect of cognition on motor cortex excitability through attention-related afferent modulation.…”
Section: Introductionmentioning
confidence: 99%
“…J Physiol 596.21 movement planning (Voller et al 2005(Voller et al , 2006Richardson et al 2008;Ni et al 2011;Asmussen et al 2013Asmussen et al , 2014Cho et al 2016). We recently reported that there is no significant relationship between afferent inhibition and tactile or motor performance (Turco et al 2018b).…”
Section: Functional Relevance Of Afferent Inhibitionmentioning
confidence: 99%
“…Indeed, alterations of SAI have been observed in association with cognitive deficits [46][47][48], movement preparation [49], modifications of cholinergic [48], GABAergic [50] and dopaminergic activity [51]. This may also account for the weak, although significant, correlation that we here report between SAI and PDGF-CSF.…”
Section: Discussionmentioning
confidence: 43%